1939
DOI: 10.1093/jn/18.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Retarded Growth, Life Span, Ultimate Body Size and Age Changes in the Albino Rat after Feeding Diets Restricted in Calories

Abstract: Diets used in these studies were made very high in percentage of such constituents as protein, minerals and vitamins in order to insure an adequate ingestion of these essentials. The retardation is effected by the deficiency in the daily allowance of energy in the diet. In the present study every animal was given the same daily allowance of the basal diet. Animals permitted t o grow normally were given additional calories.The amount of this diet fed to individuals daily was determined by the amount needed to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
131
0
4

Year Published

1983
1983
2010
2010

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 337 publications
(139 citation statements)
references
References 15 publications
4
131
0
4
Order By: Relevance
“…Calorie restriction (CR), the reduction in macronutrient intake while maintaining sufficient micronutrient intake, is one notable exception. Early studies by McCay and colleagues (1)(2)(3) established the effectiveness of CR for extending the life span of rats in the 1930s, and subsequent studies have demonstrated that sustained reductions in calorie intake can increase maximum life span in a wide range of species (4).…”
Section: A S the Quincentennial Of The 1513 Launch Of Ponce Dementioning
confidence: 99%
“…Calorie restriction (CR), the reduction in macronutrient intake while maintaining sufficient micronutrient intake, is one notable exception. Early studies by McCay and colleagues (1)(2)(3) established the effectiveness of CR for extending the life span of rats in the 1930s, and subsequent studies have demonstrated that sustained reductions in calorie intake can increase maximum life span in a wide range of species (4).…”
Section: A S the Quincentennial Of The 1513 Launch Of Ponce Dementioning
confidence: 99%
“…While a number of childhood factors, such as stress, infection and nutrition, may interrupt growth and hence result in short legs, a detailed analysis of the British 1946 birth cohort found that infant feeding was the most important childhood factor associated with leg length (Wadsworth et al, 2002). Animal studies have shown that energy restriction leads to growth retardation and decreased risk of cancer (McCay et al, 1939;Hankinson et al, 1998), and a study in humans found that lower energy intake in childhood was associated with reduced cancer risk in adulthood . The association between energy restriction in childhood and decreased breast cancer risk in adulthood may be mediated via IGF, which plays a fundamental role in somatic growth.…”
Section: Leg Lengthmentioning
confidence: 99%
“…The association may be explained by factors that jointly influence stature and breast cancer risk. These include hormones such as insulin-likegrowth factor I (IGF-I) (Hankinson et al, 1998;Kaaks et al, 2002), energy intake in childhood (McCay et al, 1939;Hart and Turturro, 1997;Frankel et al, 1998), and also intrauterine growth, reflected by birth weight, which has been found to be positively associated with breast cancer risk (Michels et al, 1996;Stavola et al, 2000;Vatten et al, 2002). Since the two components of adult height -leg length and trunk length -are poorly correlated with each other and appear to be influenced by different early life factors (Gunnell, 2002;Wadsworth et al, 2002), examining their separate associations with breast cancer may provide additional insights into the mechanisms responsible for the association between height and breast cancer.…”
mentioning
confidence: 99%
“…Growth, life span, and body size were measured in rats in response to fat and carbohydrate intake. Restriction of either macronutrient led to life span extension (McCay et al 1937). Several objections to these findings can be considered.…”
mentioning
confidence: 98%